Penyuluhan Teknik Pembuatan Lubang Biopori dalam Pencegahan Banjir di Desa Pemalongan Kecamatan Pelaihari Kabupaten Tanah Laut - Akhmad Gazali; Fathurrahman Fathurrahman; Hendra Cahyadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Land use that is not in accordance with conservation rules and exceeds the capacity of its carrying capacity, will cause critical land. The behavior of the people who have not supported the preservation of land and the environment have caused floods in the rainy season. Efforts are needed to improve the management of water resources, namely to keep the quantity of groundwater maintained so as to ensure the availability of water for the community. The development of infiltration wells and making biopore holes is intended as a medium to hold and store rainwater. Biopori holes are cheap and good environmental technology. The main capital is human desire and awareness to save their environment from water availability and water pollution. Extension of biopore hole making techniques is done by the lecture method along with questions and answers and demonstrations. The lecture method is needed to explain the concept of management efforts and the sustainability of the existence of water sources and biopore holes in general, while the question and answer to give the opportunity for participants to better understand the concept so that those who do not understand can ask. Demonstration methods are needed to clarify the process of the technique and the stages of making biopore.